Neuroprotective Effects of Ceftriaxone Involve the Reduction of Aβ Burden and Neuroinflammatory Response in a Mouse Model of Alzheimer’s Disease - Tikhonova, Maria A.; Amstislavskaya, Tamara G.; Ho, Ying-Jui; Akopyan, Anna A.; Tenditnik, Michael V.; Ovsyukova, Marina V.; Bashirzade, Alim A.; Dubrovina, Nina I.; Aftanas, Lyubomir I. (Frontiers in Neuroscience, 2021)
Ceftriaxone (CEF) is a safe and multipotent antimicrobial agent that possesses neuroprotective prop-erties. Earlier we revealed the restoration of cognitive function in OXYS rats with signs of Alz-heimer’s disease (AD)-like pathology by CEF along with its modulating the expression of genes relat-ed to system of amyloid-beta (Aβ) metabolism in the brain. The aim of this study was to determine the effects of CEF on behavior, Aβ deposition, and associated neuroinflammation using another model of an early AD-like pathology induced by Aβ. Mice were injected bilaterally i.c.v. with Aβ fragment 25-35 to produce AD model while the CEF treatment (100 mg/kg/day, i.p., 36 days) started the next day after the surgery. The open-field test, T-maze, Barnes test, IntelliCage, and passive avoidance test were used for behavioral phenotyping. Neuronal density, amyloid accumulation, and the expression of neuroinflammatory markers were measured in the frontal cortex and hippocampus. CEF exhibited beneficial effects on some cognitive features impaired by Aβ neurotoxicity including complete restoration of the fear-induced memory and learning in the passive avoidance test and im-proved place learning in the IntelliCage. CEF significantly attenuated amyloid deposition and neu-roinflammatory response. Thus, CEF could be positioned as a potent multipurpose drug as it simulta-neously targets proteostasis network and neuroinflammation as well as glutamate excitotoxicity, oxi-dative pathways, and neurotrophic function as reported earlier. Together with previous reports on the positive effects of CEF in AD models, the results confirm the potential of CEF as a promising treat-ment against cognitive decline from the early stages of AD progression.